Pupillary and affective responses to maternal feedback and the development of borderline personality disorder symptoms. (25th October 2016) - Scott, Lori N.; Zalewski, Maureen; Beeney, Joseph E.; Jones, Neil P.; Stepp, Stephanie D.
Abstract: Etiological models propose that a biological vulnerability to emotional reactivity plays an important role in the development of borderline personality disorder (BPD). However, the physiological and phenomenological components of emotional reactivity that predict the course of BPD symptoms in adolescence are poorly understood. This prospective study examines pupillary and affective responses to maternal feedback as predictors of BPD symptom development in adolescent girls over 18 months. Fifty-seven 16-year-old girls completed a laboratory task in which they heard recorded clips of their own mothers making critical or praising statements about them, as well as neutral statements that did not pertain to them. Changes in girls' pupil dilation and subjective affect were assessed throughout the task. The results demonstrated that greater pupillary response to maternal criticism predicted increases in BPD symptoms over time. In addition, greater pupillary and positive affective responses to maternal praise were associated with higher BPD symptoms at age 16 and faster decreases in BPD symptoms over time, but only among girls who heard clips that were rated by independent observers as less praising. The results suggest that emotional reactivity can serve as either a risk or a protective factor depending on context, with differential effects of reactivity to criticism versus praise.